2013
DOI: 10.1096/fj.12-220053
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HSP27 blocks fibrosis development and EMT features by promoting Snail degradation

Abstract: Idiopathic pulmonary fibrosis (IPF) is a devastating disease characterized by myofibroblast proliferation. Transition of epithelial/mesothelial cells into myofibroblasts [epithelial-to-mesenchymal transition (EMT)] occurs under the influence of transforming growth factor (TGF)-β1, with Snail being a major transcription factor. We study here the role of the heat-shock protein HSP27 in fibrogenesis and EMT. In vitro, we have up- and down-modulated HSP27 expression in mesothelial and epithelial cell lines and stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
104
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(111 citation statements)
references
References 48 publications
(73 reference statements)
5
104
1
1
Order By: Relevance
“…Consistent with its activation of E-cadherin expression, ATRA inhibited BLM-induced Snail and Twist expression, further supporting that ATRA ameliorated lung fibrosis via inhibiting EMT. Recent studies 40,43,[45][46][47] support our findings. For example, Snail and Twist are upregulated by the majority of EMT inducers and they play a crucial role in this transforming event.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with its activation of E-cadherin expression, ATRA inhibited BLM-induced Snail and Twist expression, further supporting that ATRA ameliorated lung fibrosis via inhibiting EMT. Recent studies 40,43,[45][46][47] support our findings. For example, Snail and Twist are upregulated by the majority of EMT inducers and they play a crucial role in this transforming event.…”
Section: Discussionsupporting
confidence: 90%
“…To further study the effect of ATRA on EMT, we examined the expression of Snail and Twist, two most thoroughly studied transcription factors involved in EMT. 40,41 It is believed that Snail directly inhibits E-cadherin, whereas Twist suppresses the expression of E-cadherin indirectly. 42 Gene overexpression studies have shown that Snail is sufficient to induce EMT, and snail deficiency attenuates TGF-b1-induced EMT in alveolar epithelial type II (ATII) cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSPB1 has been reported to mediate the EMT by promoting the stabilization of SNAIL in idiopathic pulmonary fibrosis and enhancing the EMT in lung cancer, leading to tumor invasion and metastasis (32,48). These findings, which contradict our results, may be explained by the different roles of the protein in normal and pathologic cells or cell-/tissue-specific patterns of expression (33).…”
Section: Discussioncontrasting
confidence: 98%
“…Targeting IL-8 may provide a novel strategy for the treatment of cancer. Previous studies have also revealed close associations between EMT and SNAIL in tumor metastasis (42)(43)(44). ZEB1, TWIST and SNAIL have also been implicated in carcinoma via the phosphatidyl inositol 3-kinase (PI3K) (45,46) and glycogen synthase kinase 3β signaling pathways (42).…”
Section: Regulation Of Emtmentioning
confidence: 98%